1964
DOI: 10.1002/jlac.19646740117
|View full text |Cite
|
Sign up to set email alerts
|

Über pflanzliche Herzgifte, XLII. Zur Konstitution des Glucobovosids A und über neue Glykoside aus Bowiea volubilis H

Abstract: Um das ungewohnliche chernische Verhalten des Glucobovosids A zu erklaren, wird eine Halbacetal-Bindung zwischen dern 6-standigen OH der Glucose und der Aldehydgruppe an C-10 des Aglykons angenommen. AuRerdern werden zwei neue Glykoside, Bovoneosid und Bovovolubosid, beschrieben.Aus den Zwiebeln von Bowiea volubilis HARVEY und B. kilimandscharica MILDBREAD sind ca. 20 verschiedene Bufadienolid-glykoside bzw. Aglykone isoliert worden 2-9), deren Konsitution nur in wenigen Fallen mit Sicherheit bestimmt ist. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…No new information has been published during this period on the bufadienolide contents of Bowiea. The known compounds from Bowiea volubilis are bovoside A 27 (a 6-deoxy-3-O-methylglucoside derivative of bovogenin A 47), glucobovoside A, 28 and bovoruboside (16-oxo-3-O--thevetosylhellebrigenin). 29…”
Section: The Bufadienolides Inmentioning
confidence: 99%
“…No new information has been published during this period on the bufadienolide contents of Bowiea. The known compounds from Bowiea volubilis are bovoside A 27 (a 6-deoxy-3-O-methylglucoside derivative of bovogenin A 47), glucobovoside A, 28 and bovoruboside (16-oxo-3-O--thevetosylhellebrigenin). 29…”
Section: The Bufadienolides Inmentioning
confidence: 99%
“…299 Katz and Tschesche et al have between them reported the presence of several bufadienolides (bovisides A 560, B, C, D, bovogenin E, bowieasubstanz G, glucobovoside A 561, nabogenin (scilliglaucosidin) 532, bovoruboside 562 and bovogenin A 563) between the years of 1950 and 1959. [300][301][302][303][304][305][306][307][308][309][310][311][312][313][314] Structures have been reported for nabogenin 532, bovoruboside 562, bovoside A 560, glucobovoside A 561 and bovogenin A 563, although the structure reported for bovoruboside is not certain. The cardioactive glycosides from B. volubilis attracted much attention in the early years of their discovery.…”
Section: The Urgineoideaementioning
confidence: 99%
“…The same anthocyanins were produced with some small changes in the percentage composition of the different compounds. 132 The red owers of H. orientalis likewise produced a range of acylated anthocyanins (303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313)(314)(315)(316) and, as with the blue owers, the red owers produced in vitro produced the same anthocyanins with some differences in composition. [133][134][135] A later investigation of the blue owers of H. orientalis revealed a further seven anthocyanins (317)(318)(319)(320)(321)(322)(323) in addition to those isolated previously.…”
mentioning
confidence: 95%